2006
DOI: 10.1021/jp065744z
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Characteristics of TiO2 and Their Relationship to the Photoassisted Reaction of Water/Methanol Mixture

Abstract: This work investigated the photoluminescence characteristics of TiO2 and discussed the relationship between the photoluminescence features of TiO2 and the photoassisted reaction of water/methanol mixture. It is found that anatase TiO2 displays a visible luminescence band centered at about 505 nm and rutile TiO2 mainly shows a near-infrared luminescence band centered at about 835 nm, which are respectively ascribed to the oxygen vacancies in anatase TiO2 and the intrinsic defects in rutile TiO2. The visible lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
263
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(283 citation statements)
references
References 50 publications
19
263
1
Order By: Relevance
“…Photoluminescence (PL) spectra of catalysts were next measured to investigate the efficiency of charge carrier trapping, migration, and transfer and the separation of photogenerated electron-hole pairs [47]. It was reported that a weaker PL emission signal is commonly indicative of higher photocatalytic activity [48,49].…”
Section: Uv-vis and Pl Analysismentioning
confidence: 99%
“…Photoluminescence (PL) spectra of catalysts were next measured to investigate the efficiency of charge carrier trapping, migration, and transfer and the separation of photogenerated electron-hole pairs [47]. It was reported that a weaker PL emission signal is commonly indicative of higher photocatalytic activity [48,49].…”
Section: Uv-vis and Pl Analysismentioning
confidence: 99%
“…The valence bands of both phases have similar energy and thus contribute to the photooxidation of methanol in the same way. Furthermore, the anatase structure is usually more defective than the rutile one, but oxygen defects are alternatively believed as efficient electron traps, enhancing charge separation [45], or undesired recombination sites [46].…”
Section: Materials and Mechanismsmentioning
confidence: 99%
“…Anatase and rutile are the two main crystalline structures of TiO 2 , with band gap energies at 3.2 and 3.0 eV, respectively. 1 The photocatalytic activity of TiO 2 depends on its surface to volume ratio and crystal structure, and several studies have been performed in order to investigate these issues. 2,3 In particular, one dimensional TiO 2 such as nanotubes is more attractive because of its large specific surface area, which has more reactive sites to absorb and oxidize pollutants such as benzene, phenol, and p-chlorophenol.…”
Section: Introductionmentioning
confidence: 99%